1993
DOI: 10.1002/chin.199321156
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reduction of Substituted 1H‐4,5‐Dihydroimidazolium Salts.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It has been previously shown that 1,3-disubstituted imidazolinium cations are reduced to the corresponding imidazolidines by relatively strong reducing agents such as Zn/HCl, 21 NaBH 4 , 22 or LiAlH 4 . 22,23 The results in this study revealed that such conversion can be performed under very mild conditions by the catalytic reaction using H 2 as a reducing agent. 24 To gain an insight into the mechanisms of the catalysis, the effects of proton acceptors and solvents were further investigated for the representative catalysts 4 and 6.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been previously shown that 1,3-disubstituted imidazolinium cations are reduced to the corresponding imidazolidines by relatively strong reducing agents such as Zn/HCl, 21 NaBH 4 , 22 or LiAlH 4 . 22,23 The results in this study revealed that such conversion can be performed under very mild conditions by the catalytic reaction using H 2 as a reducing agent. 24 To gain an insight into the mechanisms of the catalysis, the effects of proton acceptors and solvents were further investigated for the representative catalysts 4 and 6.…”
Section: ■ Introductionmentioning
confidence: 99%